Hubungan Antara Pengetahuan, Sikap Dengan Perilaku Gaya Hidup Sehat Mahasiswi Tingkat Tiga Prodi D-3 Kebidanan Universitas MH. Thamrin Jakarta Timur - Kursih Sulastriningsih; Ella Nurlelawati; Riza Umami (JOURNAL EDUCATIONAL OF NURSING(JEN), 2020)
An increase in infectious and non-communicable diseases is caused by a bad lifestyle at a young age. And much is needed enough knowledge and good attitude as early as possible to prevent the occurrence of infectious or non-communicable diseases. The study aims to determine the relationship between knowledge, aatitudes and healthy lifestyle behaviors of third-level female students of the Diploma III in Midwifery University MH Thamrin East Jakarta. This study used a cross-sectional design that was carried out for two months in the study program at Midwifery University MH Thamrin East Jakarta. Based on the result of the bivariate analysis test between the variables of knowledge with healthy lifestyle behaviors, the value of p=0,43 and OR = 1,75 shows that there is no relationship between knowledge and healthy lifestyle behavior. Atttitudes with healthy lifestyle behaviors indicate that positive attitudes have a healthy lifestyle that is higher by 90.7% (49 respondents) compored to negative attitudes have a 4 times chance of having a healthy lifestyle compared to respondents with negative attitudes. Based on the result and discussion it can be concluded that respondents with good knowledge have 2 times the opportunity to have a healthy lifestyle compared with respondents with less knowledge and respondents with a positive attitude have a 4.2 times chance of having a healthy lifestyle compared to respondents with a negative attitude